Global public governance Toward world government? - Peou, Sorpong ([Singapore] World Scientific Publishing, 2023)
Global Public Governance is a text written for students, scholars and lay people interested in learning about this global system, which emerged and has evolved in response to global challenges that no one actor can effectively address. Drawing on what has been published over the last several decades, this text highlights the importance of states and nonstate actors seeking to provide global public goods through collective action. Covering conceptual, theoretical, and empirical issues, as well as eight main themes — global security, human rights, global criminal justice, global health, global education, global finance, global trade, and the global environment — this text offers a comprehensive treatment of global public governance. It concludes that the current system remains far from effective, but world government is not a better alternative. In short, this text proposes a regional approach to global public governance.
Part I Historical, Conceptual and Theoretical Issues -- Chapter 1 What global Public Governance is -- Chapter 2 Globalization, subsystems, and global authority -- Chapter 3 Theoretical traditions and perspectives in a nutshell -- Part II The Security and Legal Dimensions -- Chapter 4 Global security governance -- Chapter 5 Global human rights governance -- Chapter 6 Global criminal justice governance -- Part III The Security and Legal Dimensions -- Chapter 7 Global health governance -- Chapter 8 Global education governance -- Part IV The Economic and Environmental Dimensions -- Chapter 9 Global finance governance -- Chapter 10 Global trade governance -- Chapter 11 Global environment governance –- Conclusion : Toward world government? : Potential benefits and drawbacks.
Includes bibliographical references and index
Keywords: International cooperation; Globalization; Internationalism